Metodologia de análise térmica e hidráulica em transformadores de potência - Barth, Nórton Daniel (2020)
The power transformers have a high importance for the eletric power system, allowing the transmission of huge amounts of energy for big lengths and reduces losses. Althought the transformers have a high eficiency, a small part of process energy are converted to losses, resulting a rise of temperature on device. The problem associated to the rise of temperature is the fact of increase the agging of solid insulation, reducing the lifetime. This study show a metodology of temperatures and oil flow calculation for the radiator and the determination of the temperature disc-to-disc in the widings, both based on the geometry of the device. The calculation techniques resulted of this two methodologies possibilitated the criation of two algorithmics for the power transfrom analysies: One focusing in the radiator and other, the widing. For validation of this metodologies was used finites elements simulation, with the porpuse of compare the temperatures of top, botton and hotspot of tranformers.